SYNTHESIS AND CHARACTERIZATION OF STRUCTURAL NANOCOMPOSITE TITANIUM DIOXIDE COPPER-DOPED USING THE IMPREGNATION METHOD - La Ode Asmin; La Isa (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
Nanocomposite Titanium Dioxide (TiO2) doped Copper (Cu), Cu-TiO2 is synthesized by the impregnation method. This study aims to determine the effect of adding Cu to the TiO2 structure. The 1, 3, and 5 Cu with% TiO2 dissolved in 50 ml of deionized water, and 3 grams of TiO2 added. The compound is then stirred for 2 hours at 90oC and dried in an oven at 110oC for 30 minutes. Drying samples were calcined at 500oC for 3 hours. Cu-TiO2 nanocomposites were characterized by XRD, SEM-EDX Mapping, and FTIR. The XRD analysis results show that Cu-TiO2 nanocomposite has a high level of crystallinity and has an anatase phase structure. The size of TiO2 crystals decreased with Cu doping and increased from 49.66 nm to 49.68 nm, with an increase in the composition of the doping mass of Cu. The SEM-EDX Mapping results show that all samples tend to clot, and Cu dopants evenly distributed on the surface of TiO2. FTIR analysis explained the presence of hydroxyl ions in the sample marked with the appearance of the absorption peak at 1658.78 cm-1 associated with OH bending of Ti-OH.